Environmental and economic issues for animal-based composites - Kamarudin, Siti Hasnah; Ridzuan, Abdul Rahim; Abu, Falah; Osman, Syaiful; Mohd Basri, Mohd Salahuddin; Hamzah, Muhammad Hazwan; Zarin, Nur Izzati; Mohd Hatta, Siti Khairiyah; Md Yusof, Nur Nadiah; Abdullah, Ummi Hani (Elsevier, 2024)
The chapter presents an overview of the environmental and economic concerns associated with animal-based composites. Animal-based composites are materials made by combining animal-derived compounds such as bone, feather, and wool with other components to generate new materials with distinct features. The environmental case investigates the environmental impact of animal agriculture, such as deforestation, habitat loss, and greenhouse gas emissions connected with the production of animal-based resources. The economic case examines both good and negative features, such as farmer income generation and resource-intensive production procedures that can result in increased costs. The lack of environmental damage costs in the pricing of animal-based composites is also explored. Natural fiber-based composites such as silk, wood, jute, and kenaf are frequently studied and discussed, whereas animal fiber-based composites are rarely investigated in depth. This chapter discusses the many groups of animal fibers, their sources, availability, qualities, and composites made from them, as well as their applications. Hence, this overview emphasizes the necessity of taking into account the environmental and economic implications of animal-based composites and urges the exploration of alternative materials to reduce environmental effects. The potential applications for animal-based composites are vast, and their development and implementation can lead to a more sustainable and prosperous future. With ongoing research and innovation, researchers can harness the full potential of animal-based composites and revolutionize various industries for the betterment of our planet and economy.